Analisis Standar Operasional Prosedur Berdasarkan Tipe Kepemimpinan di Torch Engineering - Ageng Saepudin Kanda; Serlia Ramadhani Putri (Universitas 45 Surabaya, 2024)
Almost all foundations in Indonesia or even in the world have standard work methodologies (SOPs). Not only in the context of government, education, etc., an assembly organization also requires SOPs in every part of the organization. In an organization, regulations are made in a more precise structure, namely Work System Standards or what are often called SOPs. Every organization definitely has dreams and missions to achieve, both in the short and long term. In subjective examination, the techniques commonly used are meetings, perceptions and use of notes. This research examines the concept of standard operating procedures (SOP). The focus point of this examination is on the 3 most interesting things in the SOP. Based on in-depth interviews with 10 subjects at the Torch Engineering company, it is stated that Standard Operating Procedures are the core thing in a work process as well as the type of leadership that regulates the running of a series of Standard Operating Procedures. The results of the research This provides a deeper understanding of how the type of leadership and the SOP concept are mutually sustainable in increasing the effectiveness and efficiency of work at Torch Engineering.